2017
DOI: 10.4236/ajps.2017.812207
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Morphology and Pollen Fertility Estimation of Three Medicinal Plant Species of <i>Hypericum</i> L. from Kaghan Valley, Northern Pakistan

Abstract: Pollen morphology & pollen fertility estimation of three medicinal species belonging to genus Hypericum L. from flora of Kaghan valley, Northern Pakistan was investigated by light and scanning electron microscopy for the first time. The species are Hypericum elodeoides Choisy in, Hypericum oblongifolium Choisy, and Hypericum perforatum L. Pollen morphological characteristics with considerable variation are provided for these taxa. Among the studied taxa, the pollen grains were 3-4 colporate type and the larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The second group was sph prolate, composed of two species, i.e., H. davisii and H. perforatum. Mazari et al (2017) also obtained similar results and mentioned that in the polar view, the pollen grains' shape in all the species was circular to semi-angular; however, in the equatorial view, the pollen grains were oblatespheroidal. According to the surface decoration of pollen grains examined by SEM, the isolated species under study were divided into four groups:…”
Section: Resultssupporting
confidence: 55%
“…The second group was sph prolate, composed of two species, i.e., H. davisii and H. perforatum. Mazari et al (2017) also obtained similar results and mentioned that in the polar view, the pollen grains' shape in all the species was circular to semi-angular; however, in the equatorial view, the pollen grains were oblatespheroidal. According to the surface decoration of pollen grains examined by SEM, the isolated species under study were divided into four groups:…”
Section: Resultssupporting
confidence: 55%
“…Radaeski et al (2016) [ 46 ] studied monoporate apertures in Poaceae. Pollen grains in Poaceae may provide a strong correlation among size, pore, and annulus [ 24 , 62 ]. The aperture is reported as an important feature used for the identification of closely related taxa [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reticulate, scabrate and echinate sculpturing were noticed in A. absinthium and S. kurramense which is dissimilar to Umber et al (2022) findings, who reported echinate reticulate ornamentation in P. hysterophorus and Scabrate echinate exine sculpturing in X. strumarium. According to Mazari et al (2017), pollen grain reported is circular to sub angular and echinate in X. strumarium. Attique, et al (2022): recently, described that A. vulgaris have echinate perforate exine ornamentation, which is dissimilar to the finding of the current study.…”
Section: Discussionmentioning
confidence: 99%